Sublingual misoprostol versus intramuscular oxytocin in the prevention of post partum hemorrhage - Sandoval Paredes, José (2015)
OBJETIVE: To determine whether there is a difference in the efficacy and tolerance of sublingual misoprostol and oxytocin intramuscularly in the prevention of postpartum hemorrhage. DESIGN: randomized clinical trial conducted in the "Sergio E. Benales" de Lima Hospital, during the period from January to October 2003. MATERIALS AND METHODS: The sample consisted of 136 women in labor divided into two groups: group 1, 68 patients were administered 2OOμg misoprostol sublingually and group II, 68 patients were injected with 10 IU oxytocin intramuscularly immediately after expulsion. RESULTS: In the misoprostol group, the average birth and postpartum bleeding time was 18 min 2 sec 486.6 mL; respectively, while the oxytocin 1O min 53 s and 317.12 mL on average, respectively, with statistically significant differences. significant decrease in the average hematocrit value was found before and after misoprostol supplied. By contrast, this difference with oxytocin was found. Misoprostol, 76.5% of patients had at least one cotateral effect, only 22% reported having felt some discomfort with oxytocin. CONCLUSION: In the prevention of postpartum hemorrhage oxytocin intramuscularly is more effective than misoprostol sublingually and has fewer side effects.